The effect of different suture materials on the safety of colon anastomosis in an experimental peritonitis model - Arikanoglu, Z.; Cetinkaya, Z.; Akbulut, S.; Ilhan, Y. S.; Aygen, E.; Basbug, M.; Dagli, F. (Verduci Publisher, 2013)
BACKGROUND: The aim of this experimental study was to compare the safety of different suture materials in a left colonic anastomosis in the presence of peritonitis. MATERIALS AND METHODS: Twenty-one male Wistar albino rats were randomly divided into three groups. First, left colonic injuries were created in all groups for the peritonitis model. After 24 hours, coated polyglactin 910 and silk suture were used in Group I rats, polydioxanone and silk suture were used in Group II rats, and coated polyglactin 910 plus antibacterial suture and silk suture were used in Group III rats during colonic anastomosis. Tissue hydroxyproline, anastomotic bursting pressure, and histopathologic findings on the anastomosis line were evaluated on the 10th postoperative day by performing a relaparatomy. RESULTS: The mean bursting pressure values were 198 +/- 11.37, 220 +/- 17.7, and 244 +/- 9.52 in Groups I, II, and III, respectively (Group I vs. II, p < 0.035; I vs III, p < 0.002; and II vs III, p < 0.021). The mean hydroxyproline levels were 1.21 +/- 0.58, 1.47 +/- 0.44, and 2.11 +/- 0.32 in Groups I, II, and III, respectively (Group I vs II, p < 0.338; I vs III, p < 0.011; and II vs III, p < 0.025). When histopathologic findings of the groups were compared, the healing score of the intestinal tissue was higher in Group III than in Group I (p < 0.015), whereas there were no statistically significant differences among Groups I vs II and II vs III (p < 0.081 and p < 0.095, respectively). CONCLUSION: Antibacterial suture usage increased anastomosis safety in the presence of peritonitis in resection and primary anastomosis.
Keywords: Colon anastomosis; Antibacterial suture; Peritonitis